Micro & small caps liquidity and stock return : an analysis of the US market - Rojas Martínez, Harold Gustavo (2018)
In this study we analyze the impact of different liquidity factors on the expected returns of the small caps listed in the USA stock market and find evidence that the mentioned effect exists. We show the existence of a premium driven by small caps that is not captured by the size factor but instead by their liquidity; this was done through performing linear regressions on models built as an extension of the Fama & French three-factor model. We learned that the liquidity factor exists and is bigger and statistically significant in the small caps than it is in the big caps, which corroborates what is stated in the literature. The importance of this investigation lays down in the potential application when deciding to build a portfolio that takes advantage of the liquidity effect of the small caps in addition to the standard ‘size effect’.